The cognitive shortcut that clouds decision-making - Keersmaecker, Jonas de; Schmid, Katharina; Brashier, Nadia; Unkelbach, Christian (MIT Sloan Management Review, 2022)
Business leaders are routinely confronted with bad information, and despite the common conviction that only others are vulnerable to biased judgment, they too fall prey to what researchers call the illusory truth effect. That is, merely repeating false claims increases their believability, leaving people vulnerable to basing their decisions on misinformation. This article describes the phenomenon in detail and provides guidance on how to combat this cognitive bias.